Evaluation of phosphite as a root and foliar fertilizer source of phosphorus - Bertsch, Floria (2009)
The capability of phosphite to supply P needs in –lettuce, tomato and banana – was studied. The relative effectiveness of phosphite with respect to phosphate as a source of P via roots was compared through the growth and absorption of the element by the 3 crops, growing under greenhouse conditions in nutrient solutions without P, with phosphite, with phosphate and with both of them. Under the same conditions, but on nutrient solutions without P, the foliar supply of P, and its effect on growth and absorption from 4 commercial sources and 2 of reactive-quality (one phosphite, the other phosphate), were compared on the same 3 crops. In the test for root absorption results show that P as phosphite, is non-usable for the plant to fulfill its P needs, and tends to cause injury. The combination of phosphite plus phosphate via roots tended to promote a greater total P absorption by plants; however, this experiment failed to identify the chemical form in which P is present inside the plant. Results from the foliar application of commercial phosphite and reactive-quality phosphate and phosphite show once again that it is impossible to fulfill the P needs of a crop strictly with foliar applications. On the other hand, under conditions of root-supply shortage of this element, phosphite based commercial products tested as foliar P sources failed to contribute significantly to crop growth; nor did they mitigate P-deficiency expression, nor improved the foliar absorption of this nutrient. Rather, they worsened foliage and root deterioration. The synergistic effect of root application of phosphates and phosphites, as well as the response to foliar phosphites under conditions of adequate phosphate supplement via roots–whether supplied through nutrient solution under hydroponic conditions or by soil means–deserve to be addressed in greater depth.